2019
DOI: 10.3892/ol.2019.9930
|View full text |Cite
|
Sign up to set email alerts
|

Human epidermal growth factor receptor 2 amplification as a biomarker for treatment in patients with lymph node‑metastatic penoscrotal extramammary Paget's disease

Abstract: The role of human epidermal growth factor receptor 2 (HER2) amplification as a biomarker for treatment in patients with lymph node (LN)-metastatic penoscrotal extramammary Paget's disease (EMPD) was investigated in the present study. A total of 11 male patients with LN-metastatic penoscrotal EMPD were retrospectively reviewed. Positron emission tomography/computed tomography (PET/CT) was conducted prior to surgery. Immunohistochemistry and fluorescence in situ hybridization were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Previous studies reported that 15-60% of patients with EMPD harbor HER2 amplification or overexpression. 7 And Her2-targeted trastuzumab monotherapy for EMPD patients has been described as clinical benefit with median progression-free survival (mPFS) from 6 to 12-17 months. 13,14 However, the efficacy of HER2-targeted trastuzumab in advanced EMPD patients with HER2 mutation is limited, due to the therapeutic efficacy of trastuzumab is dependent on the HER2 overexpression and gene amplification of HER2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported that 15-60% of patients with EMPD harbor HER2 amplification or overexpression. 7 And Her2-targeted trastuzumab monotherapy for EMPD patients has been described as clinical benefit with median progression-free survival (mPFS) from 6 to 12-17 months. 13,14 However, the efficacy of HER2-targeted trastuzumab in advanced EMPD patients with HER2 mutation is limited, due to the therapeutic efficacy of trastuzumab is dependent on the HER2 overexpression and gene amplification of HER2.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 However, the efficacy of HER2-targeted trastuzumab in advanced EMPD patients with HER2 mutation is limited, due to the therapeutic efficacy of trastuzumab is dependent on the HER2 overexpression and gene amplification of HER2. 7 Therefore, trastuzumab combined with paclitaxel is effective, which has been recommended for those EMPD patients with HER2 amplification or overexpression. 9 Figure 2 Next-generation sequencing (NGS) showed HER2 R678Q in exon 17, S310Y in exon 8 and S310F in exon 8; triple HER2 mutations could be observed in tissue and ctDNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 15 case reports have addressed HER2-targeted therapies against EMPD [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Most of the cases are EMPD with HER2 overexpression evaluated by IHC.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning anti-HER2 treatments for EMPD, Vornicova et al reported the HER2-targeted drug lapatinib to be effective against HER2-positive EMPD [ 13 ]. Further, several case reports have shown the HER2-targeted antibody trastuzumab alone or with cytotoxic chemotherapies to be effective against metastatic or advanced EMPD in ERBB2 -mutant or HER2/ ERBB2 -overexpressed cases ( Supplemental Table S1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Notably, Nordmann et al reported an EMPD tumor harboring the ERBB2 S310F mutation that was sensitive to anti-HER2 treatment, with the patient achieving a near-complete response by a combination treatment of trastuzumab and carboplatin [ 24 ].…”
Section: Introductionmentioning
confidence: 99%